THE IMPACT OF DAILY READING FOR LANGUAGE LEARNERS - Ismoilova Shodiya,; Firdavs Ikromov, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article examines the impact of daily reading on language learners. Research results show that regular reading plays a significant role in expanding vocabulary, acquiring grammatical structures, and developing cultural understanding.[1] The article employs a systematic review methodology to analyze 42 studies with 4,827 participants across various contexts. Findings reveal that daily reading creates a virtuous cycle of language development through both explicit and implicit learning mechanisms. The research contributes valuable insights for educational institutions, language programs, and individual learners seeking effective strategies for language acquisition. [1] Footnote 1: Cultural understanding is an important part of language learning.